Correlation Between Thyroid Dysfunctions and Pregnancy - Elrgeig, Hajer Khalil (faculty of Basic Medical Science - Libyan International Medical University, 2020)
The thyroid diseases are the most common disorders that effect the women in reproductive period due to several factors. However, if thyroid dysfunction is not treated or delayed in diagnosis in early pregnancy, they will effect both mother and fetus by sever outcomes. Moreover, the subclinical hypothyrodism is the most common thyroid disorder in pregnancy. The rate of clinical hypothyroidism was 2.4%, subclinical hypothyroidism was 11.3%, and 1.5% of pregnant women with overt hyperthyroidism, and subclinical hyperthyroidism was 0.3%. Inaddition, the best choice of treatment in pregnant women with hypothyrodism is a replacement therapy with levothyroxine, while the propylthiouracil is preferred in hyperthyrodism
Pregnancy is an important reproductive period, with reversible effects on thyroid gland in pregnant women such as: thyroid function, size, and iodine metabolism, in addition, the immune system changes can occur. (1,5) If these changes are not detected and untreated in early pregnancy, will lead to sever maternal and fetal outcomes.(2) Estimation of thyroid diseases in pregnancy is essential for normal and healthy gestational period, beacause the changes during pregnancy will lead to thyroid dysfunction.(2,4) Furthermore, thyroid function tests such as Free Thyroxine (FT4), Free triiodothyonine (FT3), thyroid-stimulating hormone (TSH), anti-thyroid peroxidase antibodies (TPO), and measurement of iodine level in urine is important in early diagnosis to prevent maternal and fetal complications